2009
DOI: 10.1074/jbc.m806193200
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Transcriptional Activity of Pregnane X Receptor by Protein Arginine Methyltransferase 1

Abstract: Pregnane X receptor (PXR) is a ligand-dependent transcription factor, regulating gene expression of enzymes and transporters involved in xenobiotic/drug metabolism. Here, we report that protein arginine methyltransferase 1 (PRMT1) is required for the transcriptional activity of PXR. PRMT1 regulates expression of numerous genes, including nuclear receptor-regulated transcription, through methylating histone and non-histone proteins. Co-immunoprecipitation and histone methyltransferase assays revealed that PRMT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 30 publications
0
50
0
2
Order By: Relevance
“…In earlier studies, we observed that many cancer cells lines derived from GI tract, such as HepG2, HT29 and HCT116, showed loss of PXR expression (Xie et al, 2009; data not shown). Upon ectopic expression of PXR through transfection, the PXR function could be restored and cells showed significant reduced proliferation, suggesting its role in controlling tumour cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies, we observed that many cancer cells lines derived from GI tract, such as HepG2, HT29 and HCT116, showed loss of PXR expression (Xie et al, 2009; data not shown). Upon ectopic expression of PXR through transfection, the PXR function could be restored and cells showed significant reduced proliferation, suggesting its role in controlling tumour cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, we noticed that in many cell lines derived from GI tract, such as HepG2 and HT29 cells, expression of PXR is lost (Xie et al, 2009). To investigate the effects of PXR on tumour cell growth, we restored PXR expression through transfection of human PXR into the HT29 colon cancer cell line.…”
Section: Loss Of Pxr In Human Colon Cancers and Restoration Of Pxr Bymentioning
confidence: 99%
“…PKA regulates NF-kB-dependent transcription with different expression levels of endogenous A-kinase interacting protein 1 (AKIP1) in multiple cell lines (Gao et al, 2010). Moreover, a recent study revealed that the histone methyltransferase, protein arginine methyltransferase 1 (PRMT1), plays a role in the transcriptional activity of PXR by controlling its cellular compartmentalization (Xie et al, 2009). A recent report also revealed that rifampicin-activated human PXR SUMOylation directly represses NF-kB in liver (Hu et al, 2010).…”
Section: Suppression Of Inflammationmentioning
confidence: 98%
“…It is recruited to 5'-region of the CYP3A4 gene to methylate histone H4 as a response to the PXR agonist rifampicin (Xie et al, 2009). CYP3A4 is also regulated by constitutive androstane receptor (CAR) albeit it at a lower rate of expression.…”
Section: Cyp2w1mentioning
confidence: 99%